2011
DOI: 10.1016/j.jfoodeng.2010.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surfactants on the functional properties of gelatin-based edible films

Abstract: a b s t r a c tThe aim of this research was to evaluate the plasticizing effect of natural surfactants lecithin or yucca extract from Yucca schidigera on gelatin-based films. Films containing yucca extract showed higher tensile strength values ($90-40 MPa) and moisture contents ($15%) and less elongation ($5%) and water vapor permeability values ($0.22-0.09 g mm m À2 h À1 kPa À1 ) compared to films containing lecithin. Soluble films ($20-50%) were obtained when yucca extract was used while lecithin produced lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
36
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(52 citation statements)
references
References 28 publications
(48 reference statements)
8
36
0
6
Order By: Relevance
“…Higher elongations, compared to those obtained in this work, have been reported previously in the literature, combining gelatin and glycerol, as plasticizer agent, for film production without the addition of surfactants [5,23] . The results confirm the absence of plasticization due to the inclusion of the surfactants used, as previously observed when films based on gelatin and the same surfactants, were produced and characterized [24] . …”
Section: Mechanical Propertiessupporting
confidence: 88%
See 1 more Smart Citation
“…Higher elongations, compared to those obtained in this work, have been reported previously in the literature, combining gelatin and glycerol, as plasticizer agent, for film production without the addition of surfactants [5,23] . The results confirm the absence of plasticization due to the inclusion of the surfactants used, as previously observed when films based on gelatin and the same surfactants, were produced and characterized [24] . …”
Section: Mechanical Propertiessupporting
confidence: 88%
“…The increased levels of surfactant tend to increase b* values, being the more pronounced effect observed for films containing yucca extract. The same effect observed before in gelatin-based films added with the same surfactants [24] . Tween 80 was used as emulsifier into carboxymethyl cellulose films containing glycerol and oleic acid, and it was observed that an increasing on oleic acid content increased b values of the films.…”
Section: Dias T P Et Al -Effect Of the Addition Of Soy Lecithin Asupporting
confidence: 83%
“…The expected tendency for these data was the decrease in WVP with increasing SL and VCO. Andreuccetti et al (2011) evaluated the effect of the surfactants SL and yucca extract (Yucca schidigera) on the WVP of gelatin-based edible films. Films containing yucca extract presented lower values of WVP when compared to the lecithin-based ones.…”
Section: Opacitymentioning
confidence: 99%
“…Emulsifiers are essential in the formation of protein-based films containing lipid molecules (Zhao 2012). Aiming the formation of a homogeneous film structure, several authors have suggested the use of surfactants such as soy lecithin and yucca extract (Andreuccetti et al 2011), Tween 40 (Kowalczyk and Baraniak 2014), glycerol monostearate, and Tween 60 and 80 (Bravin et al 2004). Soy lecithin is an amphoteric surfactant; it is composed of one or two fatty acid groups (hydrophobic) linked to a glycerol chain, a phosphate and alcohol group (hydrophilic) (Stauffer 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The possibility of recruiting Y. schidigera-derived surfactant in manufacturing gelatine-based film was assessed. 6 On extrusion, it demonstrated good solubility to produce homogeneous films. Also, it showed better water barrier properties due to the characteristic hydrophobicity of the steroidal moiety of the saponin.…”
Section: Food Additivesmentioning
confidence: 99%